Pengaruh Influencer, Citra Merk, Harga Dan Kualitas Produk Terhadap Keputusan Pembelian Produk Eiger Adventure (Studi Kasus Pada Konsumen Brand Eiger Di Kota Malang) - Pratama, Faisal Agus; Basalamah, Muhammad Ridwan; Wahono, Budi (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This research was conducted to determine and analyze the influence of influencers, brand image, price, and product quality on the purchasing decision of Eiger Adventure products. This study uses an explanatory research method with a quantitative approach, employing multiple linear regression analysis as the data analysis technique. The sampling technique used is non-probability sampling with purposive sampling, involving 120 respondents who are users of Eiger products and have previously purchased Eiger Adventure products. The results show that influencers, brand image, price, and product quality simultaneously have a significant influence on purchasing decisions, and each independent variable  influencer, brand image, price, and product quality also has a partial influence on purchasing decisions. Keywords: Influencer, Brand Image, Price, And Product Quality